Relationship between the Knowledge of Pospartum mothers and the choice of Intrauterine Device contraception method in the working area of Jongkong Health Center - Teodosia Manja Utari; Anik Sri Purwanti (Riviera Publishing, 2026)
The Family Planning program in Indonesia emphasizes the use of Long-Term Contraceptive Methods (LTCM), such as the Intrauterine Device (IUD), to ensure effective birth spacing and control population growth. However, the utilization of IUDs remains low nationally and locally. This study aimed to analyze the relationship between postpartum mothers’ knowledge and their choice of the IUD method in the working area of the Jongkong Health Center, Kapuas Hulu Regency, where IUD usage is notably the lowest (below 1%). A quantitative analytical study with a cross-sectional design was conducted from September to December 2025. The sample consisted of 36 postpartum mothers selected through accidental sampling. Data were collected using a validated and reliable questionnaire (Cronbach’s Alpha = 0.639). Statistical analysis using the Chi-Square test revealed a significant relationship between knowledge and IUD choice (p-value = 0.018). Postpartum mothers with good knowledge demonstrated an 88.9% uptake rate, compared to only 14.1% among those with insufficient knowledge. The findings conclude that knowledge is a pivotal factor influencing IUD selection. Therefore, strengthening health education interventions targeting postpartum mothers—particularly through antenatal and postnatal counseling by midwives—is crucial to improve knowledge and potentially increase the adoption of this effective long-term contraceptive method in low-coverage areas.